Lynx: A knowledge-based AI service platform for content processing, enrichment and analysis for the legal domain. Issue 106 (May 2022) - Moreno Schneider, Julián; Rehm, Georg; Montiel-Ponsoda, Elena; Rodríguez-Doncel, Víctor; Martín-Chozas, Patricia; Navas-Loro, María; Kaltenböck, Martin; Revenko, Artem; Karampatakis, Sotirios; Sageder, Christian; Gracia, Jorge; Maganza, Filippo; et al.
Abstract: The EU-funded project Lynx focuses on the creation of a knowledge graph for the legal domain (Legal Knowledge Graph, LKG) and its use for the semantic processing, analysis and enrichment of documents from the legal domain. This article describes the use cases covered in the project, the entire developed platform and the semantic analysis services that operate on the documents. Highlights: The EU project Lynx has developed a Knowledge Graph for the legal domain (LKG). The LKG interlinks a large number of documents through linguistic and semantic information. The Lynx technology platform includes a large number of semantic processing services. Multilingual services can be flexibly combined into complex tasks by a workflow manager. The three use cases benefit from the flexible Lynx platform and the multilingual LKG.